Key Topics in environmental sociology, 1990–2014: results from a computational text analysis. Issue 2 (3rd April 2018) - Bohr, Jeremiah; Dunlap, Riley E.
ABSTRACT: Environmental sociology is a growing field producing a diverse body of literature while also moving into the mainstream of the larger discipline. The twin goals of this paper are to introduce environmental sociologists to innovations in content analysis, specifically a form of text-mining known as topic modeling, and then employing it to identify key themes and trends within our diverse field. We apply the topic modeling approach to a corpus of research articles within environmental sociology, identifying 25 central topics within the field and examining their prevalence over time, co-occurrence, impact (judged by citations), and prestige (judged by journal rankings). Our results indicate which topics are most prevalent, tend to occur together, and how both vary over time. They also indicate that the highest impact topics are not the most prevalent, the most prestigious topics are not the most prevalent, and topics can be prestigious without exerting much impact. We conclude with a discussion of the capabilities computational text analysis methods offer environmental sociologists.